2021
DOI: 10.1002/jmv.27500
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant capacity as a marker of severity of COVID‐19 infection: Possible prognostic and therapeutic clinical application

Abstract: The pathogenesis of SARS‐CoV‐2 infection, causative pathogen of the known COVID‐19 pandemic is not well clarified. In this regard oxidative stress is one of the topics that need to be investigated. Therefore, the present research was performed to explore the relationship between the oxidant/antioxidant system and COVID‐19 exacerbation. Sera were collected from 120 patients with COVID‐19 infection and 60 healthy volunteers as the control group. The patient group consisted of 60 cases with mild disease and 60 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
5
23
0
Order By: Relevance
“… 45 Further, another study observed a complete depletion of the vascular antioxidant enzymatic resources in ICU COVID-19 patients. 46 In our study, the plasma lipids peroxides values were well above those observed in control subjects with cardiovascular risk factors, including metabolic syndrome, suggesting a strong oxidative stress during COVID-19. We did not observe high levels of lipid peroxidation in septic shock, commonly associated with massive inflammation-induced ROS production, 47 although we did measure a clear increase in sTREM-1 reflective of neutrophilic polymorphonuclear (PMN) activation and phagocytosis.…”
Section: Discussionsupporting
confidence: 61%
“… 45 Further, another study observed a complete depletion of the vascular antioxidant enzymatic resources in ICU COVID-19 patients. 46 In our study, the plasma lipids peroxides values were well above those observed in control subjects with cardiovascular risk factors, including metabolic syndrome, suggesting a strong oxidative stress during COVID-19. We did not observe high levels of lipid peroxidation in septic shock, commonly associated with massive inflammation-induced ROS production, 47 although we did measure a clear increase in sTREM-1 reflective of neutrophilic polymorphonuclear (PMN) activation and phagocytosis.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the alterations in the glucose-insulin axis and FA metabolism [48] may lead to an increase in OS, increased inflammation, interleukin storm, and decreased mobilization of leukocytes, phagocytic activity, TAC and impairment of endothelial function [52]. In this sense, it has been reported that the TAC levels were considerably lower in serum of mild and severe COVID-19 patients in comparison with control subjects [53]. Our results showed alterations in some markers of OS such as LPO, TAC, thiols, 8-isoprotanes, GSH, 3-NT and NO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring NO metabolite levels in a healthy individual who later contracted COVID-19 showed the same trend of reduced NO bioavailability during infection [ 149 ]. Slight decreases in serum NO metabolites were also found in another cross-sectional study comparing COVID-19 patients with controls [ 150 ]. In contrast, increased NO metabolite and nitrotyrosine levels were found in severe COVID-19 patients and non-survivors [ 149 ], suggesting excessive NO production as part of a hyperinflammatory response reported in more severe cases.…”
Section: Nitric Oxide Homeostasismentioning
confidence: 80%